Perfect Storm: DSAs Embrace Deep Learning for GPU-Based Computer Vision - Pias, Marcelo; Botelho, Silvia; Drews-Jr, Paulo (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.2019.9771, 2019)
Deep Learning methods are currently the state-of-the-art in many Computer Vision prob- lems. This 6-hour tutorial explores Deep Learning for Computer Vision through a hands- on approach. Participants will have the opportunity to apply deep neural networks (DNNs) to image classification problems through tools, frameworks and data pipelines commonly used to train and deploy DNN in a customised GPU-accelerated virtual machine. A sur- vey paper will be prepared to bring further details on the topics covered.